PEMETAAN DISTRIBUSI PEMASARAN HASIL TANGKAPAN IKAN PPN KARANGANTU (STUDI KASUS KAPAL BAGAN PERAHU) - Ardiana; Ayang Armelita Rosalia; La Ode Alam Minsaris (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
The Karangantu Archipelagic Fisheries Port, commonly referred to as PPN Karangantu, provides a venue for business activities in the field of fisheries. These business activities are carried out by the fishermen of the Boat Lift Net. The Boat Lift Net captures small pelagic fish, and the catch is distributed by the fishermen of the Boat Lift Net at PPN Karangantu to fish traders outside the Karangantu location. This expands the distribution of the marketing of the catch from PPN Karangantu, as it is not only marketed at the Karangantu Fish Auction (TPI Karangantu). Therefore, the objective of this research is to illustrate the map of the distribution locations of the marketing of the catch from the Boat Lift Net landed at PPN Karangantu. Subsequently, it aims to identify the distribution channels for the marketing of the catch from Boat Lift Net at PPN Karangantu. To achieve these objectives, this research uses a qualitative descriptive approach and Geographic Information System (GIS) with remote sensing methods. As a result, it is found that PPN Karangantu has 4 distribution channels and there are 11 distribution locations for the marketing of the catch from the Boat Lift Net